If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2x + 13 = x + 11 Reorder the terms: 13 + -2x = x + 11 Reorder the terms: 13 + -2x = 11 + x Solving 13 + -2x = 11 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 13 + -2x + -1x = 11 + x + -1x Combine like terms: -2x + -1x = -3x 13 + -3x = 11 + x + -1x Combine like terms: x + -1x = 0 13 + -3x = 11 + 0 13 + -3x = 11 Add '-13' to each side of the equation. 13 + -13 + -3x = 11 + -13 Combine like terms: 13 + -13 = 0 0 + -3x = 11 + -13 -3x = 11 + -13 Combine like terms: 11 + -13 = -2 -3x = -2 Divide each side by '-3'. x = 0.6666666667 Simplifying x = 0.6666666667
| 22=2a+5 | | a=7+15n | | a=8+15n-1 | | 2810=64t+970 | | -51.9+5.18= | | 8+7+3=55 | | an=15+8n | | 8h-15=h+6 | | 9(2y-1)=135 | | 245=35+60h | | X/-7=14 | | 8m-16=47+m | | 88+2x+x=120 | | 4x/3=-12 | | x-5/5=-2 | | (2+2)(9-7)= | | 4x-3=5/4-3x | | 42=7x-9+2x | | 2=u-2.56 | | 6(x-1)=-3(2+x)-3x+12 | | (4e^2x)+4=7 | | 3x/18x | | f(x)=-6x^2+24x-20 | | 4900=x(x)+48x | | 1/3×3.14×4×8 | | -4a+32=16 | | 90=6xn | | 1/3×3.14×2^2×8 | | -3(0.6667x-4)=14 | | -7x-8x=60 | | 20-x/2=10 | | 4+9j-8+8+7j+94= |